2018
DOI: 10.1001/jamaoncol.2018.0049
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Genetic Alterations With Response to Treatment and Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Patients With EGFR-Mutant Advanced Non–Small Cell Lung Cancer

Abstract: J. Excess body weight and the risk of primary liver cancer: an updated meta-analysis of prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
148
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(173 citation statements)
references
References 6 publications
22
148
2
1
Order By: Relevance
“…However, when all genetic variations, including both SNVs and CNVs of HER2 bypass signaling pathway, PI3K/Akt/mTOR pathway, and TP53 were analyzed, it demonstrated that multiple (two or more) genetic variations were associated with significantly worse survival compared with one or none genetic variation. Similar results were observed with concomitant genetic alterations in EGFR-mutant advanced non-small cell lung cancer (22).…”
Section: Discussionsupporting
confidence: 83%
“…However, when all genetic variations, including both SNVs and CNVs of HER2 bypass signaling pathway, PI3K/Akt/mTOR pathway, and TP53 were analyzed, it demonstrated that multiple (two or more) genetic variations were associated with significantly worse survival compared with one or none genetic variation. Similar results were observed with concomitant genetic alterations in EGFR-mutant advanced non-small cell lung cancer (22).…”
Section: Discussionsupporting
confidence: 83%
“…As mentioned before, NGS can be used to detect mutations that would otherwise be missed by regular screening methods. Besides coalterations among the five driver genes studied here, mutations in TP53 , PIK3CA , and other genes can also co‐occur with EGFR or ALK alterations, in which case they have been shown to decrease the treatment effect of TKI therapy . For patients affected by this type of coalteration, combination therapy such as TKI plus chemotherapy should be considered.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, we cannot exclude the possibility of unknown mechanisms impacting the outcomes. The pathological subtype, passenger mutations, and mutations in other genes, as well as smoking‐related genomic patterns, might influence the treatment effect. In this study, since only three of the patients harboring EGFR/ALK coalterations and receiving TKI therapy achieved PFS, we did not compare the clinical outcomes of these patients with those of the patients harboring a single EGFR or ALK alteration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Co-occurring genetic alterations might play a role in resistance mechanisms and could potentially explain the marked diversity of individual patient outcomes. 8,9 Previous studies suggested a potential role of TP53 mutations and alterations in cell-cycle genes in poor therapeutic response. [10][11][12] However, specific co-occurring genetic alterations that affect the clinical outcomes of EGFR-TKI 3rd in addition to primary driver mutations remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%